Extracellular vesicles released upon stimulation with antiphospholipid antibodies : An actual direct procoagulant mechanism or a new factor in the lupus anticoagulant paradox? (2022)
ABSTRACT: Antiphospholipid antibodies (aPL) lead to a hypercoagulable state in vivo. Paradoxically, some of these autoantibodies perform as inhibitors of the coagulation cascade in vitro (a phenomenon referred to as “lupus anticoagulant”). The presence of lupus anticoagulant has been related to an increased quantity of plasma extracellular vesicles, which may constitute a direct procoagulant mechanism in antiphospholipid syndrome. This study investigates whether or not endothelial cell-derived extracellular vesicles released upon stimulation with aPL (aPL-EDEVs) are related to a higher direct coagulation activity. Using an in vitro model of endothelium, flow cytometry and a recalcified plasma-based assay, we found that the coagulation activity of aPL-EDEVs is mainly conditioned by the lupus anticoagulant-like activity of autoantibodies. Nevertheless, in the presence of β2 glycoprotein I, a cofactor of aPL during the stimulation of endothelial cells, the coagulation activity of EDEVs is restored in a mitogen-activated protein kinase kinases 1 and 2 (MEK1/2)-dependent manner. This phenomenon was especially evident when using immunoglobulins G from patients with vascular and obstetric primary antiphospholipid syndrome who manifest refractoriness to treatment. Our findings suggest that the role of aPL-EDEVs in the antiphospholipid syndrome-related hypercoagulable state may not rely on their capacity to enhance clotting directly. While β2 glycoprotein I performs as a procoagulant cofactor and restores the coagulation activity of extracellular vesicles via MEK1/2 pathway, proportionally, autoantibodies interact with aPL-EDEVs and exhaust their coagulation properties. Further analysis is required to establish whether lupus anticoagulant-like autoantibodies opsonise extracellular vesicles and whether opsonised vesicles may lead to thrombosis by indirect means.